2017
DOI: 10.6024/jmbai.2017.59.1.1953-03
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of marine litter along the Indian beaches : A preliminary account on its status and composition

Abstract: Beach litter are man-made objects discarded directly or indirectly. This study brings out synoptic picture of status and composition of beach were found in Kerala (17), Maharashtra (12), Tamil Nadu (2), Andhra Pradesh (4), Odisha (7) and West Bengal (3). Whereas extremely littered beaches (>100 g/m 2 ) were found in Karnataka (13), Goa, Gujarat, and Andaman Island. With reference to the coastal population and per capita share of beach debris, Goa registered highest values (40.97 kg/head) and the Odisha coast r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…These studies also highlight the importance of density and distribution maps (Deidun et al, 2018); data that is not normally obtained from current OSPAR monitoring. UAV-based methods could also become interesting for highly polluted sites like Indonesia (Purba et al, 2019), India (Kaladharan et al, 2017) or the Mediterranean coasts (Vlachogianni, 2019) to give a fast overview of litter abundance and distribution to design fast removal and mitigation strategies.…”
Section: Application Of Aerial Drones As Official Beach Monitoring Methodsmentioning
confidence: 99%
“…These studies also highlight the importance of density and distribution maps (Deidun et al, 2018); data that is not normally obtained from current OSPAR monitoring. UAV-based methods could also become interesting for highly polluted sites like Indonesia (Purba et al, 2019), India (Kaladharan et al, 2017) or the Mediterranean coasts (Vlachogianni, 2019) to give a fast overview of litter abundance and distribution to design fast removal and mitigation strategies.…”
Section: Application Of Aerial Drones As Official Beach Monitoring Methodsmentioning
confidence: 99%
“…Most plastic entering the NIO is likely to end up on the coastline within a few years, and some cross into the southern hemisphere of the IO (Van Der Mheen et al, 2020). However, plastic litter abundance on the Indian coast (Kaladharan et al, 2017;Goswami et al, 2020) is lower than in other areas (e.g., Vianello et al, 2013;Maes et al, 2017). Therefore, there is a considerable disparity between the estimated plastic waste entering the NIO and the amount recorded.…”
Section: Potential Accumulation Zones In the Indian Seasmentioning
confidence: 99%
“…Contents available at Journals Home Page: www.ijzi.net environment is referred to as marine debris (NOAA, 2010;Brander et al, 2011;Kripa et al, 2016;Kaladharan et al, 2017).…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%
“…Increasing urbanization of coastal settlements as well as tourism development has resulted in unprecedented production of anthropogenic waste (Kaladharan et al, 2017). Allsopp et al (2009) reported that approximately 80% of debris originates onshore and 20% from offshore sources (Moora and Piirsalu, 2016;Pawar et al, 2016).…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%